2008
DOI: 10.1016/j.nbd.2007.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of seizure-induced ‘transcriptional channelopathy’ of hyperpolarization-activated cyclic nucleotide gated (HCN) channels

Abstract: Epilepsy may result from abnormal function of ion channels, such as those caused by genetic mutations. Recently, pathological alterations of the expression or localization of normal channels have been implicated in epilepsy generation, and termed 'acquired channelopathies'. Altered expression levels of the HCN channels--that conduct the hyperpolarization-activated current, I h --have been demonstrated in hippocampus of patients with severe temporal lobe epilepsy as well as in animal models of temporal lobe and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 53 publications
6
67
0
Order By: Relevance
“…It remains to be elucidated whether such dysregulation on a subset of ion channels is cause by a seizure-induced long-lasting deficiency of the transcriptional/translational machinery and whether these changes may lead to enhanced excitability of neuronal networks. The notion that acquired channelopathies may develop in the course of temporal lobe epilepsy is supported for recent findings in the pilocarpine model of epilepsy (Bernard et al, 2004;Dyhrfjeld-Johnsen and Soltesz, 2004;Hirose, 2006;Jung et al, 2007;Poolos, 2005;Richichi et al, 2007). For instance, it was recently reported that a progressive transcriptional channelopaty ("downregulation") of hyperpolarization-activated cation (HCN) channels occurs in dendrites of CA1 hippocampal pyramidal neurons after pilocarpine-induced SE (Jung et al, 2007).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It remains to be elucidated whether such dysregulation on a subset of ion channels is cause by a seizure-induced long-lasting deficiency of the transcriptional/translational machinery and whether these changes may lead to enhanced excitability of neuronal networks. The notion that acquired channelopathies may develop in the course of temporal lobe epilepsy is supported for recent findings in the pilocarpine model of epilepsy (Bernard et al, 2004;Dyhrfjeld-Johnsen and Soltesz, 2004;Hirose, 2006;Jung et al, 2007;Poolos, 2005;Richichi et al, 2007). For instance, it was recently reported that a progressive transcriptional channelopaty ("downregulation") of hyperpolarization-activated cation (HCN) channels occurs in dendrites of CA1 hippocampal pyramidal neurons after pilocarpine-induced SE (Jung et al, 2007).…”
Section: Discussionmentioning
confidence: 88%
“…down-regulation) remains to be determined, but it may probably involve changes in the transcription or translational machinery. For instance, it was proposed that the mechanisms for HCN1 reduction involved calciumpermeable AMPA receptor-mediated calcium influx, and subsequent activation of Calcium/ calmodulin-dependent protein kinase II (Richichi et al, 2007). Seizure-related changes in components of the transcriptional and translational machinery may contribute to dysregulation of genes and proteins in epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of HCN1 channel expression is probably a transcriptionally regulated process that involves activation of calmodulin (CaM) kinase II and Ca 2ϩ entry via AMPA receptors (322). In contrast, upregulation of HCN2 was found to be independent of CaM kinase II (322). The consequences of up-and downregulation of HCN channel subunits may be more complex than originally expected.…”
Section: Epilepsymentioning
confidence: 96%
“…The mechanism underlying changes in HCN channel expression levels in response to seizures is unclear. Reduction of HCN1 channel expression is probably a transcriptionally regulated process that involves activation of calmodulin (CaM) kinase II and Ca 2ϩ entry via AMPA receptors (322). In contrast, upregulation of HCN2 was found to be independent of CaM kinase II (322).…”
Section: Epilepsymentioning
confidence: 99%
“…One-third of the protein sample was reserved (Ϫ80°C; representing the total pool of both surface and intracellular protein), and the remaining two-thirds were precipitated with ImmunoPure immobilized Streptavidin beads (Pierce) at 4°C. Western blots were performed as previously described (16,17), using the following primary antibodies: monoclonal mouse anti-HCN1 (1:500; NeuroMab), rabbit anti-HCN2 (1:2000; Alomone), rabbit antiKv4.2 (1:2000; Abcam), anti-actin (1:200,000), and anti-synaptophysin (1:200,000). Signal intensities were analyzed using ImageTool software (University of Texas Health Science Center).…”
Section: Hippocampal Organotypic Slice Cultures and Biotinylation Assaymentioning
confidence: 99%